2018
DOI: 10.13181/mji.v27i3.1697
|View full text |Cite
|
Sign up to set email alerts
|

The combination of <em>Acalypha indica</em>–<em>Centella asiatica</em> extracts decreases the neuronal damage in hypoxia-induced hippocampal injury animal model

Abstract: Background: Approximately 80–85% of strokes are ischemic and lead to alterations in neuronal cell morphology and cell death. There is a lack of studies on the effect of the combination of Acalypha indica L. (AI) and Centella asiatica L. (CA) in terms of its neurotherapy property. This study was conducted to investigate the neurotherapeutic effect of the combination of AI–CA extracts in improving rat’s hippocampal neuron injury post-hypoxia.Methods: A total of 36 Sprague-Dawley rats were categorized into six gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…In the same study, the authors showed that asiatic acid significantly improved cell survival and enhanced mitochondrial membrane potential in an oxygen–glucose deprivation-induced HT-22 hippocampal neuronal cell line ( Krishnamurthy et al, 2009 ). Similarly, a combination of CA extracts and Acalypha indica L (AI) decreased the neuronal cell damage in the hippocampus of hypoxia-induced injury rats model ( Farida et al, 2018 ). Furthermore, a later finding showed that CA extract exhibited its anti-oxidant effects by attenuating the reduction of body length in the hypoxia-exposed zebrafish group ( Ariani et al, 2019 ).…”
Section: Hypoxia-induced Neuroinflammation: Human Alzheimer’s Disease Clinicopathological Evidencementioning
confidence: 99%
“…In the same study, the authors showed that asiatic acid significantly improved cell survival and enhanced mitochondrial membrane potential in an oxygen–glucose deprivation-induced HT-22 hippocampal neuronal cell line ( Krishnamurthy et al, 2009 ). Similarly, a combination of CA extracts and Acalypha indica L (AI) decreased the neuronal cell damage in the hippocampus of hypoxia-induced injury rats model ( Farida et al, 2018 ). Furthermore, a later finding showed that CA extract exhibited its anti-oxidant effects by attenuating the reduction of body length in the hypoxia-exposed zebrafish group ( Ariani et al, 2019 ).…”
Section: Hypoxia-induced Neuroinflammation: Human Alzheimer’s Disease Clinicopathological Evidencementioning
confidence: 99%
“…Tikus kelompokkan menjadi : kelompok kontrol tanpa treatmen sebagai kontrol negatif; kelompok perlakuan diberikan citicoline 50 mg/kgBB sebagai kontrol positif; tiga kombinasi dosis AI150-CA150, AI200 -CA150, dan AI250-CA150 mg/kgBB yang berbeda. Pemberian citicoline secara signifikan mengurangi kerusakan sel-sel saraf (30,8%); kombinasi ekstrak AI-CA dari AI150-CA150, AI200-CA150, dan AI250-CA150 juga secara signifikan mengurangi kerusakan sel-sel saraf sebanyak 36%; 36,4%; dan 30,4%, secara berurutan) dibandingkan dengan tikus kontrol (15,4%) (Farida et al 2018).…”
Section: Anti Strokeunclassified